PENGARUH SERVICE QUALITY TERHADAP CUSTOMER LOYALTY YANG DIMEDIASI CUSTOMER SATISFACTION DI E-COMMERCE - Meigy Soelyono; Moch Sabur (STMIK Widuri Jakarta, 2024)
E-commerce involves a series of processes for buying and selling goods and services online. In Indonesia, e-commerce users reached 196.47 million and are expected to increase to 244.67 million by 2027 (Statista, 2023). Tokopedia, as a significant e-commerce platform, continues to improve its service quality to maintain customer loyalty and increase the number of customers. This study analyzes the impact of service quality on customer loyalty, mediated by customer satisfaction. Using a quantitative approach with a survey method, a sample of 400 respondents who follow Tokopedia's account was obtained through the Taro Yamane formula. Data were collected through an online questionnaire and analyzed using PLS-SEM with SmartPLS software. The results show a positive and significant influence of service quality on customer loyalty, mediated by customer satisfaction. This research provides insights into the importance of service quality in enhancing customer satisfaction and loyalty on the Tokopedia e-commerce platform.